Public perceptions of deer management in Scotland: the impact of place of residence, knowledge and demographic factors. (2nd October 2021) - Whitefield, Abigail C. E.; McMorran, Rob; Paterson, James S.; Warren, Charles R.
ABSTRACT: Deer have a prominent public and political profile in Scotland because of their iconic status, environmental and socio-economic impacts, and the long-running controversies surrounding their management. However, few studies have examined public perceptions of deer management. This article investigates whether rural and urban place of residence and other demographic factors are significant influences on public perceptions of deer management. A survey ( n  = 184) in rural and urban locations in Scotland explored public perceptions of deer management in contrasting localities. Place of residence, demographic information and self-reported knowledge levels were analysed to examine their impact on perceptions. Respondents generally agreed that deer management is necessary, with fencing and culling the first and second most preferred management options. Rural or urban place of residence had a limited influence on opinions of deer management, with engagement in land-based employment playing a more important role. Self-reported understanding of deer management was the most important factor in shaping opinions; those with greater knowledge were more likely to support deer culling. The findings suggest that improved public education concerning the need for deer management would be beneficial, increasing public understanding of management practices.